Hierarchical design of nitrogen-doped porous carbon nanorods for use in high efficiency capacitive energy storage. Issue 36 (24th April 2017) - Ni, Mei; Huang, Zhenghong; Zhang, Xiaoling; Liu, Jinping; Qiao, Liang; Yang, Wen
Abstract : We report a novel synthesis route for creating 3D interconnected hierarchical porous nitrogen-doped carbon nanorods (3D-IPCRs) using 1D polyaniline nanorods as a precursor and SiO2 as a porogen. Abstract : We report a novel synthesis route for creating 3D interconnected hierarchical porous nitrogen-doped carbon nanorods (3D-IPCRs) using 1D polyaniline nanorods as a precursor and SiO2 as a porogen. The 1D carbon nanorod/SiO2 composites initially formed during carbonization further act as raw materials for a KOH activation process. After subsequent removal of the templates, as-prepared 3D-IPCRs exhibit a high specific surface area (1765 m 2 g −1 ), a large total pore volume (1.06 cm 3 g −1 ), an interconnected porous structure, and a moderate nitrogen doping (2.63 wt%). This interconnectivity is beneficial to improving ion diffusion properties and electrolyte wettability. The resulting carbon exhibits a much lower impedance resistance and smaller contact angle, compared with conventional mesoporous carbon, and thus has better electric double layer performance. As obtained 3D-IPCR electrodes achieve a high specific capacitance of 302 F g −1 at a current density of 0.05 A g −1 in 6 M KOH (two-electrode system), high coulombic efficiency (99.8%) and excellent cycling stability (92.8% of capacitance retention after 10 000 cycles) even with a high mass loading (11 mg cm −2 ) and thick electrode film (300 μm). Furthermore, the energy density of 3D-IPCRs reaches 23 W h kg −1, and the power density can be as high as 18.2 kW kg −1 when the energy density remains at 9.11 W h kg −1 in an organic electrolyte.